2010
DOI: 10.1007/s12149-010-0393-7
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of 18F-Fluoride positron emission tomography for assessment of metastatic bone tumor

Abstract: (18)F-Fluoride PET or PET/CT has excellent diagnostic performance for the detection of metastatic bone tumor, but the estimated effective dose and average cost-effective ratio are at a disadvantage compared with BS planar or BS planar and SPECT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
53
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 16 publications
1
53
0
5
Order By: Relevance
“…A meta-analysis comparing sodium 18 Ffluoride with 99m Tc-diphosphonate was published in 2010 by Tateishi et al (6). In a patient-based analysis, the pooled sensitivity and specificity of sodium 18 F-fluoride in 10 studies were 96% and 98%, respectively, whereas the pooled sensitivity and specificity of 99m Tc-diphosphonate planar, or planar plus SPECT, bone scanning in 8 studies were 57% and 98%, respectively.…”
Section: See Page 574mentioning
confidence: 99%
“…A meta-analysis comparing sodium 18 Ffluoride with 99m Tc-diphosphonate was published in 2010 by Tateishi et al (6). In a patient-based analysis, the pooled sensitivity and specificity of sodium 18 F-fluoride in 10 studies were 96% and 98%, respectively, whereas the pooled sensitivity and specificity of 99m Tc-diphosphonate planar, or planar plus SPECT, bone scanning in 8 studies were 57% and 98%, respectively.…”
Section: See Page 574mentioning
confidence: 99%
“…However, there are limited data in the literature evaluating its diagnostic performance. There are a few studies that examined the performance of 18 F-fluoride PET or PET/CT in identifying osseous metastases and reported excellent results [2,14,15]. However, we noticed that these studies had very small sample size and most studies lacked histological confirmation and direct comparison with whole-body MRI.…”
mentioning
confidence: 96%
“…Tc-diphosphonate scintigraphy [1,2]. Apparently, it seems an attractive approach to combine 18 F-fluoride PET (which has high sensitivity for the detection of osseous metastasis) with 18 F-fluorodeoxyglucose (FDG) PET (which has been established as the single most important tumor imaging modality).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is renewed clinical interest in the use of 18 F-NaF since prior technical and logistic limitations to its routine use are no longer present as the demand for 18 F-FDG promotes commercial production and delivery of 18 F-NaF. Studies have shown that 18 F-NaF PET produces images with higher sensitivity and specificity than 99m Tcbased bone scans; however, with the increasing use of 18 FNaF PET/CT in routine clinical practice for skeletal imaging in oncology [2,3], nonosseous uptake is likely to be more frequently encountered. In our case, 18 F-NaF PET/CT was Fig.…”
mentioning
confidence: 99%